Toxic stress is associated with cardiovascular disease among younger but not older women in the United States: Results from the research goes red registry - Saam Honarvar; Samaah Sullivan (Preventive Medicine Reports)
Introduction: Psychosocial stress may be an under-recognized risk factor for cardiovascular disease among younger women (ages 35–54 years). Methods: Data was obtained from the Research Goes Red Registry, initiated in 2019, and included women from the United States. Women self-reported diagnoses of cardiovascular disease and experiences of toxic stress defined as a significant life-defining stressful activity over a prolonged period unaccompanied by sufficient social resources. Logistic regression models were used to estimate odds ratios between toxic stress and cardiovascular disease and differences by age (< 55 versus ≥ 55 years of age) using an interaction term. Results: The analytic dataset included 1346 women. The mean age of women was 47.8 (SD: 12.6), 71 % were less than 55 years of age, 83 % were Non-Hispanic White, 59 % indicated that they had experienced toxic stress, and 12 % had cardiovascular disease. In final multivariable models, there were significant differences in the association between toxic stress and cardiovascular disease by age group (toxic stress-by-age interaction = 0.0412) such that toxic stress was only significantly associated with an increased odds of cardiovascular disease among women < 55 years of age (OR: 1.79; 95 % CI: 1.03, 3.11) but not older women ≥ 55 years of age (OR: 0.82; 95 % CI: 0.49, 1.39). Conclusion: Toxic stress was associated with an increased odds of cardiovascular disease among younger, but not older women in this cross-sectional study. Stress may be an under-recognized risk factor for cardiovascular disease, especially among younger women who may benefit from interventions to mitigate and prevent stress.